(untitled) - Hyndman, Donald (Belmont, CA, 2006)
Natural disasters are a terrible reality of our world. But with the latest scientific research you can at least be better prepared. NATURAL HAZARDS AND DISASTERS, 2005 HURRICANE EDITION walks you through the major earth and atmospheric hazards that can appear suddenly, helping you be informed and make smart choices. And, with loads of illustrations, diagrams, and photos, this disasters textbook has all the resources to master the material and succeed in the course.
Keywords: Natural disasters,Disasters,Environmental risk assessment,Emergency management; United states,United states,United states